Analisis Usaha Sapi Potong Dengan Pola Kemitraan Antara Investor (Pemodal) Dengan Petani Peternak (Penggaduh) di Kelurahan Sail Kecamatan Tenayan Raya Kota Pekanbaru - Armunanto '; Jum’atri Yusri; Cepriadi ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Beef cattle is a contributor to the meat of ruminant meat production groups nationwide that farming has the potential to be developed as a profitable business. The development of the cattle business partnerships is one alternative for farmers increase profits. The Partnership is a collaboration between agribusiness start of the process of preproduction, production to marketing that is based on the principle of mutual need and benefit for those who partnered. Beef cattle business partnerships between investors with livestock farmers (penggaduh) in the Village District of Sail Tenayan Raya such Pekanbaru City is expected to increase beef production nationally, which until now have not been able to meet the growing needs of the community. Partnerships occur at the study site in the form of silent partnerships (sillent partner) where the investor share in the profits and losses (if any) on the business, but is not involved in managing the business and the involvement of investors are rarely made ​​public. Investors usually only provide capital. Based on the analysis of the business, the average yield amounted to 24 people petrnak farmers by maintaining 8 bali male head of cattle during the time period of Rp. 73,554,167, -. The average amount of the cost of Rp. 55,393,295, - So the average profit of Rp. 18,160,871, - Where the benefits applied with a 50:50 sharing system then each receive Rp. 9,080,436, - This paper aims to determine the profits to the beef cattle business partnership. Keywords: Beef cattle, partnerships, tenayan raya.